Diastematomyelia - A Case Report - Ayten Türcan,; Saadet Yazgan Umut,; Mustafa Akif Sarıyıldız, (Archives of Rheumatology, 2009)
Diastematomyelia - a congenital anomaly accompanied by multiple skeletal anomalies - is characterized by division of the neural chest into two. With somatic growth over an adult's lifetime, it might cause back pain, waist pain and neurological symptoms due to a strained cord. (Turk J Rheumatol 2009; 24: 113-5)